2016
DOI: 10.1108/jhom-10-2014-0180
|View full text |Cite
|
Sign up to set email alerts
|

Key success factors behind electronic medical record adoption in Thailand

Abstract: Purpose The purpose of this paper is to investigate the elements that health care personnel in Thailand believe are necessary for successful adoption of electronic medical record (EMR) systems. Design/methodology/approach Initial qualitative in-depth interviews with physicians to adapt key elements from the literature to the Thai context. The 12 elements identified included things related to managing the implementation and to IT expertise. The nationwide survey was supported by the Ministry of Public Health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Good understanding of user's attitude about the system was found the key factor needed to make EMR systems adopt easily. Studies identified that even good technology could be fallen if the intended users have not a positive attitude towards the system [ 17 ]. According to some studies [ 7 ], the slow rate of EMR implementation suggests that resistance among physicians was strong because Physicians are the main frontline user-group of EMRs.…”
Section: Introductionmentioning
confidence: 99%
“…Good understanding of user's attitude about the system was found the key factor needed to make EMR systems adopt easily. Studies identified that even good technology could be fallen if the intended users have not a positive attitude towards the system [ 17 ]. According to some studies [ 7 ], the slow rate of EMR implementation suggests that resistance among physicians was strong because Physicians are the main frontline user-group of EMRs.…”
Section: Introductionmentioning
confidence: 99%
“…In Lao PDR, there was a health screening project under the Thai Lao collaboration [ 30 ] but there were no routine services provided for Lao people. Another explanation of differences may be that the electronic health information system to support medical services in Lao PDR is still faced with difficulties [ 31 ], while Thailand has a successfully implemented electronic medical database [ 32 ]. With the limited national health insurance coverage in Lao PDR [ 6 ], most Lao diabetes patients pay out-of-pocket for the services and medications [ 7 ], while diabetes patients in Thailand do not pay for their services and medication which is covered by national health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Dukungan IT yang cepat penting untuk menangkap tentang masalah yang diindentifikasi dan mampu menanggapinya dan memperbaiki dengan cepat. Persepsi dukungan manajemen mengacu pada sejauh mana pengguna percaya bahwa manajemen telah berkomitmen untuk keberhasilan penggunaan sistem, dan manajemen diharapkan terus berkonsultasi dengan dokter tentang proses adaptasi sistem baru (Narattharaksa et al, 2016;Sharma & Yetton, 2007). Menurut dokter spesialis pada penelitian ini, manajemen melakukan intervensi dengan menyediakan sumber daya seperti fasilitas pendukung sistem dan memberikan arahan secara langsung dalam menggunakan fitur EMR, hal ini senada yang disampaikan (Narattharaksa et al, 2016;Venkatesh & Bala, 2008).…”
Section: Kendala Integrasi Sistemunclassified